The Effect of Learning Motivation on Mathematics Learning Achievement of Class XI Students of SMK Negeri 2 Pematangsiantar T.A 2022/2023 - Saragih, Marikris Natalia; Siahaan, Theresia Monika; Sidabutar, Ropinus (EduMatika: Jurnal MIPA, 2022)
The purpose of this study was to determine whether there was an influence of learning motivation on Mathematics Learning Achievement of class XI students of SMK Negeri 2 Pematangsiantar which consisted of 30 students. This research uses quantitative research with Quasi Experimental design research method. The population in this study was class XI as many as 9 classes at SMK Negeri 2 Pematangsiantar as many as 544 students. The number of samples taken was 30 students, namely class XI TAV-2. Data collection techniques using questionnaires and pre-test and post-test. The results of the study were to determine how much influence learning motivation had on mathematics learning achievement for XI grade students of SMK Negeri 2 Pematangsiantar T.A 2022/2023. Learning achievement based on pre-test and post-test questions is high with an average score of 75.50 and 79.33